The faint host galaxies of CIV absorbers at z > 5 - Finlator, Kristian (2020)
We explore the expected galaxy environments of CIV absorbers at z > 5 using the Technicolor Dawn simulations. These simulations reproduce the observed history of reionization, the z ~ 6 galaxy stellar mass function, the Ly a forest transmission at z > 5, and the Si IV column density distribution (CDD) at z ~ 5.5. None the less, the CIV CDD remains underproduced. Comparison with observed CII/Si II equivalent width ratios and the CII line incidence suggests that a low carbon yield accounts for some, but not all, of the CIV discrepancy. Alternatively, a density-bounded escape scenario could harden the metagalactic ionizing background more dramatically even than binary stellar evolution, boosting the CIV CDD into near agreement with observations. In this case, galaxies ionize more efficiently and fewer are required to host a given high-ionization absorber. Absorbers´ environments therefore constrain ionizing escape. Regardless of the escape scenario, galaxies correlate with CIV absorbers out to 300 proper kpc (pkpc). The correlation strengthens independently with galaxy luminosity and CIV column density. Around strong systems (log(NCIV/cm-2) > 14)), the overdensity of galaxies with MUV < -18 or log (LLy a/erg s-1) > 41.9 declines from 200-300 within 100 pkpc to 40-60 within 250 pkpc. The previously suggested association between strong CIV absorbers and Ly a emitters at z > 5 is not expected. It may arise if both populations inhabit large-scale voids, but for different reasons. Although most neighbouring galaxies are too faint for HST, JWST will, with a single pointing, identify ~10 neighbouring galaxies per strong CIV absorber at z > 5. Ground-based tests of these predictions are possible via deep surveys for Ly a emission using integral field units.